Design and manufacture the outer shell of diesel furnace - Tuan Mohd Shakir, Abu Bakar (2010)
There are a lot of diesel furnaces on the market today. The diesel furnace that is more synonymous with the duty of non-ferrous metal melting. Today, this material has been readily adopted into the diesel furnace which has a different function and form designing. However, there is no diesel furnace designs and inventions that have various functions in the market. By creating a diesel furnace is functional, is expected not only to attract the attention of consumers because of the nature and function more effectively but also can help users to work more comfortably by using a tool only and is not directly save costs and time expense of consumers. The results showed the original objectives of the project to produce diesel furnace and various functions can be used for a variety of situations is achieved. Any problems and suggestions related to the products discussed in this final chapter.